(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this research is to see the results of learning mathematics on flat shapes material after using a realistic mathematics approach in class V of SD Negeri 101766 Bandar Setia. The research method used is Classroom Action Research (CAR). The CAR model used consists of 4 stages, namely planning, action, review (observation), and reflection. The subjects in this study were 22 students of class V-B of SD Negeri 101766 Bandar Setia, consisting of 10 male students and 12 female students. The data collection technique used in this study was observation and test analysis. The results of the study from the implementation of two cycles showed that the percentage of student learning activities increased by 60% in cycle I to 88.5% in cycle II. The percentage of student learning outcomes also increased from 59% (good) in cycle I to 86% (very good) in cycle II. Based on the results of the data analysis obtained, it can be concluded that the realistic mathematics approach can improve student learning outcomes in the mathematics subject of flat shapes material in class V of SD Negeri 101766 Bandar Setia